The Correlation between Alvarado Score and Histopathological Profile of Appendicitis in Academic Hospital of Universitas Gadjah Mada - Noviana Nugrohowati; Agung Widianto; Zum Zakiyyah Itsnaini; Satya Ulan Indra Mahardhika; Rifa Sulistyani (Academic Hospital Journal, 2022)
Background: Appendicitis is an inflammation of the appendix vermiformis, which is the most common cause of acute abdominal emergency and requires immediate surgical treatment. Anamnesis and clinical examinations in Alvarado score results can be used as early detection to determine further treatment. The use of histopathological examination is to confirm the diagnosis of appendicitis. This study was to determine the correlation between the Alvarado score and the histopathological profile of appendicitis. It assesses appendicitis diagnosis accuracy based on the Alvarado score at the Academic Hospital of UGM.Methods: This study was a cross-sectional design study with a diagnostic test method using secondary data from 173 appendicitis patients from 1 January to 31 December 2019, who met the inclusion and exclusion criteria.Results: According to the histopathology result, the finding of acute appendicitis was 95.95%, which Alvarado score of ≥7 was 71.68%. The overall sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of Alvarado score for acute appendicitis were 73.49%, 71.43%, 73.41%, 98.39 %, 10.20%, respectively. Conclusion: The Alvarado score is a sensitive, specific, and accurate scoring system that functions as a diagnostic tool for acute appendicitis.